Performance analysis of protection devices in electrical power distribution system: Eko Electricity Distribution Company as a case study - Awuwoloye, Philip Oludele; Adejumobi, Isaiah Adediji; Adebisi, Oluwaseun Ibrahim; Ismaila, Salami Olasunkanmi (International Journal of Advances in Applied Sciences, 2023)
One of the major challenges hindering the effective operation of the electricity distribution system is the malfunctioning of the protection scheme. Therefore, in this study, the performance of an interrupter (oil circuit breaker (OCB)) on the Eko Electricity Distribution Company (EKEDC) network was assessed. Five-year outage data (2014 to 2018) regarding tripping of the interrupter on fault and health conditions were collected from the EKEDC Agbara/Badagry Business Unit. The tripping frequency was compared. Inspection of selected OCBs within the considered network was conducted over the study period. A breakdown voltage (BDV) test was carried out on six oil samples each for 11 and 33 kV OCB using Megger OTS60PB. The highest tripping frequency of 75 and 10 were observed in 2014 and 2018 respectively when the interrupter tripped on fault and healthy conditions. The lowest tripping frequency was, however, observed in 2018 with values of 46 and 7 respectively when the interrupter tripped on fault and healthy conditions. The inspection conducted revealed carbonized OCB contacts. The BDV test showed that two oil samples each violated the standard value of 40 kV for 11 and 33 kV OCBs respectively. This study indicated that the defective oil samples required filtration or complete replacement.